An Arts Organization Policy Brief on Indigenous Knowledges - Sy, waaseyaa’sin Christine; Qwal’qaxala, Yuxwelupton; Trépanier, France; Hirtle, Eli; Campbell, Charles; Loria, Mark; Mok, Rance; Sen, Raj (KULA)

(untitled) (University of Victoria Libraries, 2021)
This policy brief provides an overview of Indigenous knowledges for an arts organization on the Pacific West Coast in Canada. To orient readers, the brief is contextualized within the broader arc of the organizations' history of commitments to, departures from, and re-engagement with commitments to decolonization and decolonial practice. It provides a list of additional resources.